Type A personality, sleep quality, and cerebral small vessel disease: investigating the mediating role of sleep in a community-based study - Zhou, Xirui; Huang, Hao; Qu, Wensheng; Yu, Zhiyuan; Zhao, Jing; Wu, Lingshan; Zhang, Yi; Kong, Qianqian; Wang, Ziyue; Luo, Xiang (Frontiers in Neurology, 2023)
Purpose: Type A Behavior Pattern (TABP) is a personality type characterized by rapid speech, imp atience, competition, and hostility. Asymptomatic cerebral small vessel disease (CSVD) is often end emic in older adults. Individuals with TABP commonly experience suboptimal sleep quality, and a c orrelation exists between sleep disturbances and CSVD. We investigated the relationship between TABP and CSVD markers and further explored the mediating role of sleep quality in the relationshi p between TABP and CSVD. Methods: A cross-sectional survey included 764 community-dwelling adults aged 55-85 years. The TABP Scale and the Pittsburgh Sleep Quality Index (PSQI) were use d to assess personality and sleep quality, respectively. Linear and logistic regression analyses were u sed to examine relationships between variables of interest. In addition, mediation analyses with boot strapping were used to test whether sleep quality mediated the relationship between TABP and CSV D. Results: Of the 764 participants (median age 65 (61-69) years, 59.9% female), the population wi th type A personality accounted for 44.8%. After adjusting for covariates, TABP scores (p = 0.03) a nd PSQI scores (p < 0.001) were significantly correlated with CSVD. In addition, sleep quality parti ally mediated the association between type A behavior and CSVD, and the mediating effect was 10. 67%. Conclusion: This study showed that type A behavior was a risk factor for CSVD among older community-dwelling adults, and that sleep quality mediated the relationship between type A behavi or and CSVD. Changing type A behavior may help improve sleep quality, which may in turn reduce the prevalence of CSVD.